An Analysis of Demographic Characteristics and Female Workers Productivity Toward Family Income - Haryadi, H (Jurnal Trikonomika, 2011)
work in foreign venture company located in Purbalingga, Central Java. Despite of it, this research also has the aims to know the motivation, work productivity and woman workforce revenue contribution to their family income. This research is a descriptive qualitative research. Their family poor economic condition is the matter that motivates most of them to work. Their work productivity is affected by their working status in the company and also the time that they spent to work everyday. This woman workforce mostly can give revenue contribution from 50% until 100% to their family income. From this research results we can conclude that there have been a displacement role from woman workforce in Purbalingga, Central Java (especially that work in foreign venture company). Now, they not just became a household wife but they working to support their family income. Even most of them have become their family main income source (family economic backbone).